2021
DOI: 10.3389/fphar.2021.729414
|View full text |Cite
|
Sign up to set email alerts
|

Naringin Exerts Therapeutic Effects on Mice Colitis: A Study Based on Transcriptomics Combined With Functional Experiments

Abstract: Naringin has been shown to exert protective effects in an animal model of ulcerative colitis, but detailed mechanisms remain unclear. This study aimed to investigate function and signaling mechanisms underlying naringin-induced therapeutic effects on colitis. Two mouse models were established to mimic human Inflammatory bowel disease (IBD) by treating drinking water with dextran sodium sulphate or intra-colonic administration of 2, 4, 6-trinitrobenzene sulfonic acid. Transcriptomics combined with functional ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…DSS and 2, 4, 6-Trinitrobenzene sulfonic acid (TNBS) are the two most commonly used colitis inducers. Among them, DSS-induced colitis is a classical acute inflammatory model characterized by the dysfunction of the mucosal barrier, while TNBS-induced colitis is a chronic inflammation mediated by T-cell immunity which can maintain a long time ( Dong J. et al, 2021 ; Dong J. Y. et al, 2021 ). In this study, using DSS-induced colitis model, we found that DCL treatment effectively attenuated DSS-induced colitis, which mainly manifested as weight loss, colon length shortening, inflammatory cell infiltration, and colonic barrier injury.…”
Section: Discussionmentioning
confidence: 99%
“…DSS and 2, 4, 6-Trinitrobenzene sulfonic acid (TNBS) are the two most commonly used colitis inducers. Among them, DSS-induced colitis is a classical acute inflammatory model characterized by the dysfunction of the mucosal barrier, while TNBS-induced colitis is a chronic inflammation mediated by T-cell immunity which can maintain a long time ( Dong J. et al, 2021 ; Dong J. Y. et al, 2021 ). In this study, using DSS-induced colitis model, we found that DCL treatment effectively attenuated DSS-induced colitis, which mainly manifested as weight loss, colon length shortening, inflammatory cell infiltration, and colonic barrier injury.…”
Section: Discussionmentioning
confidence: 99%
“…After sequencing, the filtered reads were aligned to the tomato genome (ITAG3.0). The mapped reads, differential expression, and gene enrichment were analysed as described previously [ 64 ].…”
Section: Methodsmentioning
confidence: 99%
“…Forty-eight Balb/c male mice weighing about 16–26 g were obtained from a local source and kept in metabolic cages at 22–26 °C, 55–62% relative humidity, 12 h light, with free access to food and tap water ad libitum. Mice were randomized into six equal groups each of 8 mice by a laboratory technician who was unaware of the nature of the study as follows: control untreated group; DSS-induced colitis group drank distilled water containing 4% w/v DSS for 7 days [ 21 ]; DSS + CMC group received 0.5 mL CMC 1.5% solution by oral gavage; DSS + Perindopril group received perindopril by oral gavage in a dose of 1 mg/kg/day [ 22 ]; DSS + Ambrosin group received ambrosin by oral gavage in a dose of 10 mg/kg/day [ 18 ]; DSS + Perindopril + Ambrosin group was treated with perindopril concomitantly with ambrosin by oral gavage in the fore-mentioned doses. Treatment with CMC, perindopril, and ambrosin started one week before administration of DSS and continued during the administration of DSS.…”
Section: Methodsmentioning
confidence: 99%